Enfoque sobre el mundo del derecho : constitución y derechos fundamentales - Ferreyra, Raúl Gustavo (2013)
"On August 24, 2011, the Superior Council of the University of Buenos Aires, through Resolution 3033, appointed me as a full professor, part-time, of Constitutional Law, Department of Public Law, Faculty of Law. This writing is my inaugural lecture in the position of professor. A version: An Approach to the Legal World. Constitution and Fundamental Rights, was published in the Jahbuch Des Öffentlichen Rechts Der Gegenwart, Neue Folge, Band 60, Mohr Siebeck, pp. 21-38, Germany, 2012. And in Portuguese: Constituição e direitos fundamentalais: um enfoque sobre o mundo do directo, Porto Alegre, Linuz, 2012. It was also announced in our native language in Contextos, a publication of the Public Law Seminar of the Ombudsman's Office of the City of Buenos Aires, no. 1, Buenos Aires, 2011, pp. 40-61. The reader now has in his or her hands the revised and expanded version with the complete bibliography, including a general outline. I once again thank Professors Dr. Mary Beloff and M. Laura Clérico for their constant encouragement and initiative in facilitating scientific dialogue and publication. "-- stems directly from human nature. Modern constitutions are a clear example of technically developed legal systems. The fundamental rights established in the Argentine federal Constitution are significant lines of action which set limits and bonds that must not be violated by using the force of the State. Consequently, as language is subject to grammar and architecture is based on space rules, in the same way the use of the force of the State must be governed by the fundamental rights contained in constitutions, the logic of force.